2016
DOI: 10.1002/etc.3579
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish embryo tolerance to environmental stress factors—Concentration–dose response analysis of oxygen limitation, pH, and UV‐light irradiation

Abstract: During the last century the increase in the mean global temperatures has been shown to impact on freshwater physicochemical parameters such as pH, dissolved oxygen, or ultraviolet (UV) light abundance. Changes in these parameters could modify the toxicity of environmental pollutants. Therefore, in the present study, the authors studied the tolerance (survival and sublethal endpoints) of zebrafish (Danio rerio) embryos to variations in pH (3-12), dissolved oxygen (3.9-237 μmol/L) and UV intensity (55-467 mW/m )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 69 publications
3
12
0
Order By: Relevance
“…Even if the studies were conducted according to OECD test guideline 236 (Organisation for Economic Co‐operation and Development ), pH control would not be assured because the guideline is based on an unbuffered International Organization for Standardization (ISO) water as test medium and requires that the pH does not vary by more than 1.5 pH units in the range of 6.5 to 8.5 (Organisation for Economic Co‐operation and Development ). Zebrafish embryos can tolerate pH values between 5 and 10 (Andrade et al ), so a large shift in pH may go unnoticed in controls but may affect IOC speciation and resulting effects in test treatments. Bittner et al () demonstrated that Good’s buffers are suitable to adjust the pH within the range that is tolerable for zebrafish embryos.…”
Section: Ph Dependence Of Aquatic Toxicity Of Iocsmentioning
confidence: 99%
“…Even if the studies were conducted according to OECD test guideline 236 (Organisation for Economic Co‐operation and Development ), pH control would not be assured because the guideline is based on an unbuffered International Organization for Standardization (ISO) water as test medium and requires that the pH does not vary by more than 1.5 pH units in the range of 6.5 to 8.5 (Organisation for Economic Co‐operation and Development ). Zebrafish embryos can tolerate pH values between 5 and 10 (Andrade et al ), so a large shift in pH may go unnoticed in controls but may affect IOC speciation and resulting effects in test treatments. Bittner et al () demonstrated that Good’s buffers are suitable to adjust the pH within the range that is tolerable for zebrafish embryos.…”
Section: Ph Dependence Of Aquatic Toxicity Of Iocsmentioning
confidence: 99%
“…Mortality of positive controls was in the expected toxicity range (between 30 and 80%). Oxygen concentration and pH were above the limits described by Andrade et al [40] for developmental retardation and other sublethal effects (dissolved oxygen ≥ 6 mg/L; pH between 6 and 8). Thus, observed effects have to be considered effects of the exposure to sediment-bound chemicals and no other physical stressors.…”
Section: Fet Quality Controlmentioning
confidence: 55%
“…In the present study, the pH and dissolved oxygen level were 7.6 and 6.86 respectively. Zebrafish embryo tolerance to limited oxygen and pH level was [17]. Embryo survival appeared to be relatively resistant to oxygen depletion with a 96h-LC50 of 0.42 mg/L.…”
Section: On Water Quality Parameters During Thementioning
confidence: 99%
“…investigated by Andrade et al, [17], Median h) of 3.68 and 10.21 were determined for acid and alkaline pH, Embryo survival appeared to be relatively resistant to oxygen depletion with a mg/L. However, they the concentration level of 6mg/L and below caused oedema and developmental…”
mentioning
confidence: 97%